Stakeholders in systems problems. (1st January 2012) - Hester, Patrick T.; Bradley, Joseph M.; Adams, Kevin MacG.
Stakeholders exist at the centre of all systems problems and are the principal contributors to the solution of these problems. We provide an approach for classifying stakeholders and determining an appropriate level of action to take with respect to these stakeholders that combines the power, legitimacy and urgency typology with a stakeholder attitude classification schema. The newly developed stakeholder strategy is a matrix that combines stakeholder attitude and classification. This matrix serves as a guide for the application of resources in support of stakeholder involvement. This technique provides systems practitioners with a means to deal with stakeholders effectively.